Batas Perlindungan Hak Merek Dagang terhadap Suku Cadang Refurbished dalam Industri Reparasi Elektronik: Studi Kasus Apple Inc. Vs. Henrik Huseby - Lutfu Lanisya (Jurnal Hukum Lex Generalis, 2026)
The development of the electronic repair industry has raised legal issues regarding the use of refurbished spare parts containing original trademarks. This study analyzes trademark protection on refurbished spare parts through the case of Apple Inc. v. Henrik Huseby and its relation to the right to repair concept. The study finds that trademark protection is limited by the exhaustion of rights principle, yet the use of refurbished components may still constitute trademark infringement when it creates misleading impressions and consumer confusion. Therefore, trademark protection should be applied proportionally by considering consumer rights, transparency and sustainable repair practices.